Al Hassan-Daniel and Another v. Revenue and Customs Commissioners (JUSTICE Intervening). (2016) - Unknown
Abstract : 451 Human rights — Right to life — Prohibition of torture — European Convention on Human Rights, 1950, Articles 2 and 3 — Obligations on States — Damages for breach — Claims for breach — Standing — Who constitutes a victim — Causation Relationship of international law and municipal law — Treaties — European Convention on Human Rights, 1950 — Human Rights Act 1998 — Criminality defence — Application of common law defences to Convention claims — The law of England